(untitled) (Academia Science Repository, 2023)
The article presents the results of studying the chemical composition of mulberry fruit and mulberry molasses made from it. The amount of carbohydrates and dietary fibers, as well as proteins, fats, a number of vitamins and minerals contained in mulberry molasses was determined and analyzed.